PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KARAKTER GENERASI MILENIAL - Munawir; Risma Diah Juwanti (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
Education is an effort to improve knowledge obtained from formal and non-formal educational institutions in order to attract qualified personnel The aim of education determines the success of the process of forming a quality human being without ignoring the role of other factors in education. Islamic religious education is the most important pillar in forming the character, morals and religious understanding of Muslims. However, in the era of information and communication technology that continues to develop, Islamic religious education faces new challenges. These changes include changes in the way students search for and interact with religious information and the way teachers provide religious instruction. This research uses a qualitative approach with literature review. The aim of this research is the role of Islamic religious education teachers in improving the character of the millennial generation to understand in depth how Islamic religious education teachers can play a role in shaping the character of the millennial generation in accordance with religious values and the demands of the times. The results and discussion in this journal, namely in the education system law number 20 of 2003, defines education as a basic and planned process to create an atmosphere of learning and learning so that students can actively develop the spiritual strength of self-control and character potential. The teacher's role in increasing student learning motivation is through a process delivers teaching that creates and implements enjoyable and healthy learning conditions and provides evaluation.